ANALISIS DETERMINAN SETENGAH PENGANGGURAN DI SUMATERA BARAT - Syahri Fauzi; Dewi Zaini Putri; Alpon Satrianto (Universitas Negeri Padang, 2018)
This study aims to determine the effect of education level, occupation, employment sector, wages, age, gender, marital status, area of residence of the underemployment in West Sumatra Province. This type of research is descriptive, where this study uses secondary data in the form of a cross-section with the 2015 national labor force survey data and uses the Logistic Regression analysis method. The results of this study indicate that the level of education has a negative and insignificant effect on voluntary underemployment in West Sumatra, the field of work has a negative and not significant effect on voluntary underemployment in West Sumatra, the employment sector has a positive and insignificant effect on voluntary unemployment in West Sumatra Wages have a positive and significant effect on voluntary underemployment in West Sumatra, age has a positive and significant effect on voluntary underemployment in West Sumatra, gender has a negative and significant effect on voluntary underemployment in West Sumatra, marital status has a positive and insignificant effect on underemployment voluntarily in West Sumatra, the area of residence has a negative and insignificant effect on voluntary unemployment in West Sumatra. Keywords: underemployment, economic factor, demographic, dan logistic regression